Perceptions and awareness of dental students toward oral tissues: A cross-sectional study - Harsh Dadhich; Manisha Sardar Ahire; Saurabh Rajesh Nagar; Vijayalaxmi Nimma (Wolters Kluwer Medknow Publications, 2023)
Background: If oral mucosal lesions are detected early by the oral health practitioners, there will be a better prognosis for the lesions diagnosed. This cross-sectional study was designed to assess the perceptions and awareness of dental students of the Government Dental College and Hospital, Mumbai, toward oral tissues. Materials and Methods: A questionnaire was created to assess the perceptions and awareness of dental students towards oral tissues. This questionnaire had 25 questions with multiple choices. Options of these questions were based on 3-point and 5-point Likert scale. This questionnaire was converted into a Google Form and distributed among all the undergraduate students of the Government Dental College and Hospital, Mumbai, along with a declaration form via electronic methods such as Gmail and WhatsApp, after explaining to them the aim and objectives of the study. Results: A total of n = 334 dental students responded, yielding a response rate of 66.8%. Most dental students agreed that it is important to focus on oral soft tissues apart from oral hard tissues. Most participants believed that it is the role of the dentist to perform the complete oral examination. Lack of training, confidence, time, etc., were seen as barriers to at least some degree by participants. Conclusion: This study highlights the awareness of oral soft tissues among dental students and the importance of its academic reinforcement. This would definitely help budding dentists to work more on oral cancer prevention and detection, which ultimately may lead to a decrease in the incidence of oral cancers.